Representasi Tokoh Orang Tua dalam Film Na Willa Sebagai Bentuk Penguatan Pendidikan Karakter Anak - Priyono; Sanudin Ranam; Ibnu Fiqhan Muslim (CV. Biha Cendekia, 2026)
The increasing moral and character challenges faced by children in the digital era, coupled with changes in parenting practices and reduced parental supervision, have become significant concerns in education. At the same time, films offer considerable potential as educational media that can strengthen character education through the representation of parental figures. This study aims to describe the representation of parents in the film Na Willa as a means of strengthening children's character education. The research employed a qualitative approach using content analysis. The data source was the film Na Willa, written by Reda Gaudiamo. Data were collected by observing, identifying, classifying, and analyzing scenes portraying parental parenting practices in character formation. The findings reveal that the representation of parents in Na Willa embodies five core values of character education: religiosity, nationalism, independence, mutual cooperation, and integrity. These values are reflected through warm and empathetic parenting, effective communication, exemplary behavior, and the encouragement of children's responsibility and independence. The study concludes that Na Willa can serve as an educational medium and a practical reference for parents in fostering children's character development within the family environment.